Efektivitas Media Clay dalam Pengenalan Geometri Anak Usia Dini di TK Al-Umari - Dian Sari, Lia; Amilda, Amilda; Atika, Nyimas; Soraya, Nyayu; Oktamarina, Lidia (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze the effect of using clay media on improving the ability to recognize geometry in children aged 5-6 years at Al-Umari Kindergarten. The background of this study is based on the lack of stimulation given to children related to the introduction of geometric shapes in daily learning activities. This study uses a quantitative approach with an experimental method, as well as a one group pretest-posttest design. Data were collected through observation, testing, and documentation. The test instrument consisted of a pretest and posttest using Student Worksheets (LKPD) that had been tested for validity and reliability. The results of the analysis showed a significant increase in the ability to recognize geometry, with an average pretest score of 20.1 and increasing to 28.9 in the posttest. These findings indicate that clay media is effective in improving children's cognitive abilities in recognizing geometric shapes. In conclusion, clay media can be used as an alternative learning media that is interesting and useful for the development of early childhood cognitive abilities in the field of geometry